(x+9).(x^2-4) = 0 aaaaaaaaaaaaaaaaaaaaaaaaaaaa

(x+9).(x^2-4) = 0 aaaaaaaaaaaaaaaaaaaaaaaaaaaa

2 bình luận về “(x+9).(x^2-4) = 0 aaaaaaaaaaaaaaaaaaaaaaaaaaaa”

  1. Giải đáp + Lời giải và giải thích chi tiết:
    ( x + 9 ) * ( x^2 – 4 ) = 0
    -> x + 9 = 0 hoặc x^2 – 4 = 0
    Với : x + 9 = 0
    x + 9 = 0
    x = 0 – 9
    x = -9
    Với x^2 – 4 = 0
    x^2 – 4 = 0
    x^2 = 0 + 4
    x^2 = 4
    x^2 = 2^2
    -> x = 2
    Vậy x in {-9 ; 2}
    ~nhungan~

    Trả lời
  2. @Grey
    (x+9).(x^{2}-4)=0
    =>x+9=0 hoặc x^{2}-4=0
    TH1: x+9=0
    x=0-9
    x=-9
    TH2: x^{2}-4=0
    x^{2}=0+4
    x^{2}=4
    $\left[\begin{matrix} x=2\\ x=-2\end{matrix}\right.$
    Vậy x={-9;-2;2}

    Trả lời

Viết một bình luận

Câu hỏi mới